AUTOMATIC TRANSFER SWITCH UNTUK RUMAH TINGGAL SEDERHANA BERBASIS ARDUINO NANO - Abdi Rayatman; Yusnaini Arifin; Sari Dewi; Mardiansyah Mardiansyah (Foristek, 2021)
Automatic Transfer Switch (ATS) is a device that can move the main power source to a backup power source automatically and quickly when the main power source experiences a disturbance or cut-off of supply to the load. In this study, ATS was designed based on the Arduino Nano microcontroller as an automatic control that works based on voltage readings. Using the Arduino Nano microcontroller can facilitate the process of making tools and minimize the use of components. This ATS uses the PZEM-004T voltage sensor module. The voltage sensor module functions to detect and measure the value of the PLN voltage. From the test results, it was found that the time lag between the PLN supply being cut off until the generator was turned on and ready to load was an average of 2.76 seconds. Meanwhile, the time lag when the PLN supply turns on again until the generator supply is cut off and the load supply is again served by PLN is an average of 1.74 seconds. All working status of this ATS panel can be displayed on the LCD indicator, indicator light and analog voltmeter.